Phytotoxicity Activities of Essential Oil of Pinus sylvestris against Zea mays, Solanum lycopersicum, and Vigna unguiculata as Potential Bio-pesticides in Africa - Hezekiah Awojide, Shola; Temitayo Ajayi, Grace; Adenike Oyewole, Kehinde; Solomon Tayo, Adeniyi; Emmanuel Adeleke, Adebayo; Olumide Fadunmade, Ezekiel (Asian Health, Science and Technology Reports, 2023)
The chemical composition of the essential oil of Pinus sylvestris (Scots pine), as well as its phytotoxicity action against Zea mays, Vigna Unguiculata, and Solanum lycopersicum, were investigated in this study. The essential oil from twigs of P. sylvestris was extracted using the hydro-distillation method. The major component of the essential oil was characterised by GC/MS, and the inhibitory phytotoxicity of the essential oil formulation at varying concentrations (1, 2, 3, 4, 5 mL/L) was determined by measuring the length of the shoots and the roots of tested plants. The phytotoxicity effect of the essential oil formulations on the three seeds was also determined on the foliar as well as the root site of the three seedlings by recording the number(s) of seedlings which were distressed. The major chemical constituents are mainly oxygenated monoterpenes. The compounds are Longifolene (5.45%), Borneol (6.72%), β -terpineol (14.07%), Terpinen-4-ol (21.82%) and α-terpineol (27.17%). The root and shoot inhibitory toxicity indicated that phytotoxicity was highest on the seeds of V. unguiculata. A varying degree of toxicity was reported on the activity of the essential oil on the leaves of the seedlings of Z. mays, S. lycopersicum and V. unguiculata after 24 hr. S. lycopersicum got the lowest level of toxicity when tested on the roots and leaves of seedlings. The seedlings of Z. mays and V. unguiculata showed 100% distress when 4 mL/L of the essential oil formulation was applied, while S. lycopersicum recorded 30% distress of seedlings. All phytotoxicity activities observed were time and dose-dependent. The essential oil of P. sylvestris showed appreciable phytotoxicity activity against the three tested plants; hence, it may be considered to be a potential bioherbicide.